Gel generator and preparation method thereof
By introducing shape gradient, modulus gradient and charge gradient into the hydrogel, the problem of weak electrical signal output of existing hydrogel generators is solved, significantly improving the electrical signal output, and achieving more efficient mechanical energy conversion.
Patent Information
- Application Number
- CN202411274162.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
AI Technical Summary
The electrical signal output of existing hydrogel generators is weak, difficult to directly utilize, and the conversion efficiency of mechanical ion energy is low.
A multi-gradient hydrogel is designed to generate an electric field by introducing shape gradients, modulus gradients and charge gradients into the gel, and ion migration and charge gradients are used to generate an electric field, which significantly improves the output of the electric signal.
By controlling the gradient changes in the modulus, charge concentration and equivalent diameter of the gel, the electrical signal output of the gel generator is significantly improved, achieving more efficient mechanical energy conversion.
Smart Images

Figure CN119298721A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano energy, and in particular to a gel generator and a preparation method thereof. Background Art
[0002] At present, the main power generation methods of power generation systems are hydropower, thermal power, solar power, chemical power, nuclear fuel power, etc. These power generation methods not only consume a lot of natural resources and cause a lot of pollution, but also increase the cost of power generation and electricity consumption due to the large loss of power generation resources and current during transportation. With the gradual popularization and miniaturization of contemporary microelectronics and nanoelectronics products, nanogenerators have emerged.
[0003] Nanogenerators are the smallest generators in the world that convert mechanical energy into electrical energy within the nanometer range. Currently, nanogenerators can be divided into three categories: one is piezoelectric nanogenerators, which use the piezoelectric properties and semiconductor properties of special nanomaterials to convert bending and compression mechanical energy into electrical energy; one is friction nanogenerators, which use two materials with different electronic comfort abilities to gain or lose electrons when in contact with each other to generate current in the external circuit; and one is pyroelectric nanogenerators.
[0004] Mechanical energy-electrical energy conversion has become one of the key methods for energy harvesting, force sensing, self-powered or wearable electronic devices. Traditional mechanical-electrical energy conversion mechanisms mainly include electromagnetic effect, piezoelectricity, flexoelectricity and friction nanogenerators, etc. The generator based on the piezoelectric effect mechanism is a new type of mechanical energy-electrical energy conversion device, which relies on the difference in ion migration inside ion monomers to generate an electric field, providing a new alternative for low-frequency energy harvesting and flexible self-powered electronic devices. Although various ion conductor materials such as polypyridine composite films, ion gels and hydrogels have been reported to have piezoelectric effects, their electrical signal output is still limited to a few millivolts or tens of millivolts, making it difficult to directly use this electrical energy. Therefore, it is of great significance to further improve the conversion of mechanical ion energy. Summary of the invention
[0005] Considering that electrical signals come from the polarization of ions under mechanical stress, introducing gradient structures into ion conductors is a feasible strategy. The present invention designs a multi-gradient hydrogel to enhance the conversion of mechanical ion energy, and simultaneously introduces three gradients (shape gradient, modulus gradient, and charge gradient) into the same hydrogel. When the hydrogel is compressed, a strain gradient is formed due to the shape gradient and modulus gradient. Then the ions tend to migrate with the flow of the fluid in the hydrogel, and the combination of the difference in ion migration rate and the electrostatic force caused by the charge gradient produces ion polarization, thereby forming an electric field. The schematic diagram of its action is shown in the figure. Figure 1Compared with the uniform hydrogel, the electrical signal output of the multi-gradient hydrogel is significantly improved.
[0006] The purpose of the present invention is to overcome the problem that the electrical signal output of the hydrogel in the prior art is weak and difficult to be directly utilized, and to provide a gel generator and a preparation method thereof, wherein the gel generator has the characteristics of strong electrical signal output.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a gel generator, which includes two electrodes and a gel or a gel array sandwiched between the two electrodes, wherein at least one of the modulus, charge concentration and equivalent diameter of the gel changes gradiently from top to bottom, wherein the gradient change of the modulus includes: the cross-linking agent concentration is distributed in a gradient increasing manner from top to bottom; the change of the charge concentration includes: the charge concentration is distributed in a gradient decreasing manner from top to bottom; the change of the equivalent diameter includes: the equivalent diameter is distributed in a gradient increasing manner from top to bottom.
[0008] The second aspect of the present invention provides a method for preparing the gel generator described in the first aspect, the method comprising the following steps: S1, preparing at least two groups of solutions by evenly distributing gel monomers, initiators, ionic compounds, optionally cross-linking agents, optionally negative charge donors and solvents; or S1, preparing at least two groups of solutions by evenly distributing gel monomers, initiators, ionic compounds, optionally negative charge donors and solvents, adding cross-linking agents to each group of solutions, so that the concentration of cross-linking agents in each group of solutions is different; or S1, preparing at least two groups of solutions by evenly distributing gel monomers, initiators, ionic compounds, optionally cross-linking agents and solvents; Prepare at least two groups of solutions, add a negative charge donor to each group of solutions, so that the concentration of negative charge donor in each group of solutions is different; or S1, divide the gel monomer, initiator, ionic compound and solvent equally to prepare at least two groups of solutions, add a cross-linking agent and a negative charge donor to each group of solutions, so that the concentration of cross-linking agent and the concentration of negative charge donor in each group of solutions are different; S2, under polymerization conditions, form each group of solutions in S1 into one, and obtain a gel with at least one of modulus, charge concentration and equivalent diameter changing gradually from top to bottom; S3, sandwich the prepared gel between two electrodes.
[0009] Through the above technical solution, the present invention has the following advantages:
[0010] The gel generator of the present invention significantly improves the electrical signal output of the gel generator by controlling at least one of the modulus, charge concentration and equivalent diameter of the gel to change in a gradient from top to bottom. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 This is a schematic diagram of the effect of a multi-gradient hydrogel according to a preferred embodiment of the present invention;
[0012] Figure 2Schematic diagram of a uniform hydrogel and hydrogels with different gradients according to an embodiment of the present invention;
[0013] Figure 3 This is a structural characterization of a multi-gradient hydrogel according to a preferred embodiment of the present invention. It can be seen that the multi-gradient gel has shape gradient, modulus gradient and charge gradient at the same time;
[0014] Figure 4 It is a schematic diagram of a 3D printed multi-gradient hydrogel and its series-parallel array according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] The present invention provides a gel generator, which comprises two electrodes and a gel or a gel array sandwiched between the two electrodes, wherein at least one of the modulus, charge concentration and equivalent diameter of the gel changes in a gradient from top to bottom, wherein the gradient change of the modulus comprises: the cross-linking agent concentration is distributed in a gradient increasing manner from top to bottom; the change of the charge concentration comprises: the charge concentration is distributed in a gradient decreasing manner from top to bottom; and the change of the equivalent diameter comprises: the equivalent diameter is distributed in a gradient increasing manner from top to bottom.
[0017] The gel generator of the present invention significantly improves the electrical signal output of the gel generator by controlling at least one of the modulus, charge concentration and equivalent diameter of the gel to change in a gradient from top to bottom.
[0018] In the present invention, schematic diagrams of uniform hydrogels, shape gradient hydrogels, modulus gradient hydrogels, dual gradient (shape gradient and modulus gradient) hydrogels, and multi-gradient (shape gradient, modulus gradient, and charge gradient) hydrogels are shown in FIG. Figure 2 shown.
[0019] According to a preferred embodiment of the present invention, at least two of the modulus, charge concentration and equivalent diameter of the gel change in a gradient from top to bottom, preferably the equivalent diameter and modulus and / or charge concentration of the gel change in a gradient from top to bottom, and more preferably the modulus, charge concentration and equivalent diameter of the gel change in a gradient from top to bottom. By adopting the above preferred scheme, the electrical signal output of the gel generator can be further improved.
[0020] According to a preferred embodiment of the present invention, the gel comprises at least one of a hydrogel, an ionic gel, and an organic hydrogel, preferably a hydrogel.
[0021] In order to further improve the electrical signal output of the gel generator, according to a preferred embodiment of the present invention, based on the total mass of the polymer in the gel, the mass fraction of each gradient of the cross-linking agent in the gel is 0.1-5wt%, for example, it can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% and 4.5wt%, and the concentration increment of the cross-linking agent in adjacent gradients is preferably 0.1-5wt%, for example, the increment is 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% and 4.5wt%, and more preferably the increment is 0.5-1wt%.
[0022] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the number of levels of the gradient increase of the cross-linking agent concentration. The following is an exemplary description, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the gradient increase of the cross-linking agent concentration includes 2-8 levels of gradient increase, preferably 3-5 levels of gradient increase.
[0023] According to a preferred embodiment of the present invention, based on the total mass of the polymer in the gel, the mass fraction of each gradient of charge concentration is 0-50wt%, for example, it can be 0.5wt%, 1wt%, 5wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and 45wt%, preferably, the decreasing range of the charge concentration of adjacent gradients is 5-40wt%, for example, the decreasing range is 8wt%, 12wt%, 18wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% and 45wt%, more preferably the decreasing range is 10-15wt%. By adopting the above preferred scheme, the output of the electrical signal of the gel generator can be further improved.
[0024] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the number of levels of the gradient decrease of the charge concentration. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the gradient decrease of the charge concentration includes 2-8 levels of gradient decrease, preferably 3-5 levels of gradient decrease.
[0025] In order to further improve the electrical signal output of the gel generator, according to a preferred embodiment of the present invention, the equivalent diameter of each gradient is 7.5-20mm, for example, 8mm, 10mm, 12mm, 14mm, 15mm, 17mm and 19mm, and the increment of adjacent equivalent diameters is preferably 0.5-5mm, for example, the increment is 0.8mm, 1.2mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm, 4mm and 4.5mm, and more preferably the increment is 1-2.5mm.
[0026] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the number of stages of the gradient increase of the equivalent diameter. The following is an exemplary explanation, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the gradient increase of the equivalent diameter includes 2-8 levels of gradient increase, preferably 3-5 levels of gradient decrease.
[0027] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the number of gels in the gel array. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the gel array is a series and / or parallel arrangement of 1-16 gels.
[0028] In the present invention, the polymer in the gel is a conventional choice in the art, and the following exemplary description is given, but the scope of the present invention is not limited thereby. According to a preferred embodiment of the present invention, the polymer in the gel is a polypropylene polymer and / or a polyethylene polymer, preferably at least one of polyacrylamide, polyvinyl alcohol, polyhydroxyethyl acrylate and polyacryloyl glycinamide.
[0029] In the present invention, there is no particular requirement for the type of the cross-linking agent. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the cross-linking agent is selected from at least one of N,N-methylenebisacrylamide, ethylene glycol diacrylate and ethylene glycol dimethacrylate, preferably N,N-methylenebisacrylamide.
[0030] In the present invention, the negative charge donor in the gel is a conventional choice in the art. The following exemplary description is not intended to limit the scope of the present invention. According to a preferred embodiment of the present invention, the negative charge donor in the gel is at least one of 2-acrylamide-2-methylpropane sulfonic acid, sodium polystyrene sulfonate, sodium alginate, sodium polyacrylate, and hyaluronic acid, preferably 2-acrylamide-2-methylpropane sulfonic acid.
[0031] In the present invention, the gel contains an ionic compound, wherein the diffusion coefficients of anions and cations are greatly different, for example, the cations in the ionic compound are selected from hydrogen and alkali metal ions, and the anions are selected from halogen ions, OH - and TFSI - At least one of, specifically, can be selected from at least one of LiCl, NaCl, LiTFSI, HCl, NaOH and LiOH, preferably LiCl and / or NaCl.
[0032] In the present invention, the electrode is a conventional choice in the art, and the following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the electrode is at least one of a gold electrode, a carbon electrode, a platinum electrode, a silver electrode, a copper electrode, a stainless steel electrode and a glassy carbon electrode.
[0033] The gel generator that meets the above requirements of the present invention can achieve the purpose of the present invention. There is no special requirement for its preparation method. The following exemplary description is not intended to limit the scope of the present invention. The present invention provides a preparation method of the gel generator, which comprises the following steps: S1, preparing at least two groups of solutions by evenly distributing gel monomers, initiators, ionic compounds, optional cross-linking agents, optional negative charge donors and solvents; or S1, preparing at least two groups of solutions by evenly distributing gel monomers, initiators, ionic compounds, optional negative charge donors and solvents, adding cross-linking agents to each group of solutions, so that the concentration of cross-linking agents in each group of solutions is different; or S1, distributing gel monomers, initiators, ionic compounds, optional negative charge donors and solvents; The gel monomer, initiator, ionic compound, optional cross-linking agent and solvent are evenly prepared into at least two groups of solutions, and a negative charge donor is added to each group of solutions so that the concentration of negative charge donor in each group of solutions is different; or S1, the gel monomer, initiator, ionic compound and solvent are evenly prepared into at least two groups of solutions, and a cross-linking agent and a negative charge donor are added to each group of solutions respectively, so that the concentration of cross-linking agent and the concentration of negative charge donor in each group of solutions are different; S2, under polymerization conditions, each group of solutions in S1 is formed into one body to obtain a gel in which at least one of modulus, charge concentration and equivalent diameter changes gradiently from top to bottom; S3, the prepared gel is sandwiched between two electrodes.
[0034] In the present invention, the gel after molding can be in the shape of a truncated cone, a prism, or a hemispherical shape.
[0035] In the present invention, there is no special requirement for the initiator. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the initiator is at least one of photoinitiator 1173, photoinitiator 2959 and photoinitiator 184.
[0036] In the present invention, the solvent is at least one of water, ionic liquid and organic solvent.
[0037] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the amount of the gel monomer. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, based on the mass amount of the solvent when feeding, the amount of the gel monomer is 10-30wt%.
[0038] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the amount of the initiator. The following is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, based on the mass amount of the gel monomer at the time of feeding, the amount of the initiator is 0.1-1wt%.
[0039] According to a preferred embodiment of the present invention, the molar concentration of the ionic salt in the hydrogel is 0.5-2 mol / L.
[0040] In the present invention, the purpose of the present invention can be achieved as long as polymerization is carried out. The polymerization conditions can be conventionally selected in the art. The following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the polymerization conditions include: irradiation under ultraviolet light with a wavelength of 365nm for 30-60s.
[0041] In the present invention, the electrical output test of the gel was conducted at 10-50% compression and 0.1-2 Hz frequency.
[0042] The present invention will be described in detail below by way of examples. In the following examples,
[0043] The voltage and current were measured by a Keithley 6517B electrometer;
[0044] The compression movement was controlled by a Yuelian YLS71 mechanical machine; unless otherwise specified, the raw materials were all commercially available.
[0045] Example 1
[0046] First, three precursor solutions (named P1-P3) were prepared, including the following components:
[0047]
[0048] The specific preparation steps are:
[0049] (1) Add 1.69 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0050] (2) The above solution was divided into three equal parts, and 0.01 g, 0.02 g, and 0.03 g of N,N-methylenebisacrylamide were added respectively. The mixture was stirred for 5 minutes in the dark. The mixtures were named P1-P3.
[0051] (3) The P1-P3 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 9.5 mm, the diameter increment was 1 mm, and the height was 10 mm. From top to bottom, they were P1-P3, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0052] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 0.2 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0053] Example 2
[0054] First, four precursor solutions (named P1-P4) were prepared, including the following components in mass ratio:
[0055]
[0056] The specific preparation steps are:
[0057] (1) Add 3.38 g lithium chloride, 4 g acrylyl glycinamide and 0.02 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0058] (2) The above solution was divided into 4 equal parts, and 0.001, 0.011, 0.021 and 0.031 g of N,N-methylenebisacrylamide and 0.5, 0.35, 0.2 and 0.05 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively. The mixture was stirred in the dark for 5 minutes and named as P1-P4.
[0059] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and cylindrical gels were printed in layers with a radius of 10 mm and a height of 10 mm, which are P1-P4 from top to bottom. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0060] (4) The prepared gel was sandwiched between two platinum electrodes and compressed by 50% at a frequency of 0.1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0061] Example 3
[0062] First, five precursor solutions (named P1-P5) were prepared, including the following components in mass ratio:
[0063]
[0064]
[0065] The specific preparation steps are:
[0066] (1) Add 1.17 g of sodium chloride, 8 g of acrylamide, 0.08 g of N,N-methylenebisacrylamide and 0.04 g of photoinitiator 1173 to 40 ml of deionized water and stir for 5 minutes in the dark.
[0067] (2) The above solution was divided into five equal parts, and 0.64, 0.48, 0.32, 0.16 and 0 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively. The mixture was stirred for 5 minutes in the dark. The parts were named P1-P5.
[0068] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridge of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 10 mm, the lower radius was 20 mm, the radius increment was 2.5 mm, and the height was 10 mm. From top to bottom, they were P1-P5, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 50 seconds to form the gel.
[0069] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 10% at a frequency of 0.5 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0070] Example 4
[0071] For the preparation of single gradient-shape gradient hydrogels, four precursor solutions (named P1-P4) were first prepared, which included the following components in terms of mass ratio:
[0072]
[0073]
[0074] The specific preparation steps are:
[0075] (1) Add 0.845 g lithium chloride, 6 g acrylamide, 0.06 g N,N-methylenebisacrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0076] (2) The above solution was divided into 4 equal parts and named P1-P4.
[0077] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form; the schematic diagram of the obtained hydrogel with a gradient shape is shown in FIG. Figure 2 shown.
[0078] (4) The prepared gel was sandwiched between two carbon electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0079] Example 5
[0080] For the preparation of single gradient-modulus gradient hydrogels, four precursor solutions (named P1-P4) were first prepared, which included the following components in terms of mass ratio:
[0081]
[0082] The specific preparation steps are:
[0083] (1) Add 0.845 g of sodium chloride, 6 g of acrylamide and 0.06 g of photoinitiator 1173 to 40 ml of deionized water and stir for 5 minutes in the dark.
[0084] (2) The above solution was divided into 4 equal parts, and 0.03, 0.06, 0.09 and 0.12 g of N,N-methylenebisacrylamide were added respectively, and stirred for 5 minutes in the dark. The parts were named P1-P4.
[0085] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and cylindrical gels were printed in layers, with a radius of 10 mm and a height of 10 mm, respectively P1-P4 from top to bottom. The polymerization conditions included: irradiation under ultraviolet light of 365 nm wavelength for 45 s to form; the schematic diagram of the obtained modulus gradient hydrogel is shown in FIG. Figure 2 shown.
[0086] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0087] Example 6
[0088] For the preparation of single gradient-charge gradient hydrogel, four precursor solutions (named P1-P4) were first prepared, which included the following components in terms of mass ratio:
[0089]
[0090] The specific preparation steps are:
[0091] (1) Add 0.845 g lithium chloride, 6 g acrylamide, 0.06 g N,N-methylenebisacrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0092] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively, and the parts were named P1-P4.
[0093] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and cylindrical gels were printed in layers with a radius of 10 mm and a height of 10 mm, which are P1-P4 from top to bottom. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0094] (4) The prepared gel was sandwiched between two carbon electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0095] Example 7
[0096] To prepare the multi-gradient hydrogel, four precursor solutions (named P1-P4) were first prepared, which included the following components in terms of mass ratio:
[0097]
[0098] The specific preparation steps are:
[0099] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0100] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively, and the parts were named P1-P4.
[0101] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0102] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1. The schematic diagram of the effect of the multi-gradient gel is shown in Figure 1 shown.
[0103] Example 8
[0104] To prepare the double gradient gel, three precursor solutions (named P1-P3) were first prepared, including the following components:
[0105]
[0106] The specific preparation steps are:
[0107] (1) Add 1.69 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0108] (2) The above solution was divided into three equal parts, and 0.01 g, 0.05 g, and 0.09 g of N,N-methylenebisacrylamide were added respectively. The mixture was stirred for 5 minutes in the dark. The mixtures were named P1-P3.
[0109] (3) The P1-P3 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 9.5 mm, the diameter increment was 1 mm, and the height was 10 mm. From top to bottom, they were P1-P3, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0110] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 0.2 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0111] Example 9
[0112] First, four precursor solutions (named P1-P4) were prepared, including the following components in mass ratio:
[0113]
[0114] The specific preparation steps are:
[0115] (1) Add 3.38 g lithium chloride, 4 g acrylyl glycinamide and 0.02 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0116] (2) The above solution was divided into 4 equal parts, and 0.001, 0.011, 0.021 and 0.031 g of N,N-methylenebisacrylamide and 0.5, 0.45, 0.40 and 0.35 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively. The mixture was stirred in the dark for 5 minutes and named as P1-P4.
[0117] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and cylindrical gels were printed in layers with a radius of 10 mm and a height of 10 mm, which are P1-P4 from top to bottom. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0118] (4) The prepared gel was sandwiched between two platinum electrodes and compressed by 50% at a frequency of 0.1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0119] Example 10
[0120] First, five precursor solutions (named P1-P5) were prepared, including the following components in mass ratio:
[0121]
[0122] The specific preparation steps are:
[0123] (1) Add 1.17 g lithium chloride, 8 g acrylamide, 0.08 g N,N-methylenebisacrylamide and 0.04 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0124] (2) The above solution was divided into five equal parts, and 0.64, 0.48, 0.32, 0.16 and 0 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively. The mixture was stirred for 5 minutes in the dark. The parts were named P1-P5.
[0125] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridge of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 10 mm, the lower radius was 12 mm, the radius increment was 0.5 mm, and the height was 10 mm. From top to bottom, they were P1-P5, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 50 seconds to form the gel.
[0126] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 10% at a frequency of 0.5 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0127] Embodiment 11
[0128] First, four precursor solutions (named P1-P4) were prepared, including the following components:
[0129]
[0130]
[0131] The specific preparation steps are:
[0132] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0133] (2) The above solution was divided into 4 equal parts, and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively. The mixture was stirred for 5 minutes in the dark. The mixtures were named P1-P4.
[0134] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridge of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the cone was 7.5 mm, the lower radius was 12 mm, the diameter increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form; the schematic diagram of the obtained double-gradient hydrogel is shown in FIG. Figure 2 shown.
[0135] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0136] Example 12
[0137] First, four precursor solutions (named P1-P4) were prepared, including the following components in mass ratio:
[0138]
[0139] The specific preparation steps are:
[0140] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0141] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively. Stir for 5 minutes in the dark. The parts were named P1-P4.
[0142] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and cylindrical gels were printed in layers with a radius of 10 mm and a height of 10 mm, which are P1-P4 from top to bottom. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0143] (4) The prepared gel was sandwiched between two platinum electrodes and compressed by 50% at a frequency of 0.1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0144] Embodiment 13
[0145] First, four precursor solutions (named P1-P4) were prepared, including the following components in mass ratio:
[0146]
[0147] The specific preparation steps are:
[0148] (1) Add 0.845 g lithium chloride, 6 g acrylamide, 0.06 g N,N-methylenebisacrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0149] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid were added respectively, and the parts were named P1-P4.
[0150] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0151] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0152] Embodiment 14
[0153] To prepare the multi-gradient hydrogel, four precursor solutions (named P1-P4) were first prepared, which included the following components in terms of mass ratio:
[0154]
[0155] The specific preparation steps are:
[0156] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0157] (2) The above solution was divided into 4 equal parts, and 0.75, 0.45, 0.225 and 0 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.0075, 0.015, 0.03 and 0.045 g of N,N-methylenebisacrylamide were added respectively, and the parts were named P1-P4.
[0158] (3) The P1-P4 precursor solutions were respectively injected into the ink cartridge of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form; the schematic diagram of the obtained multi-gradient gel is shown in FIG. Figure 2 As shown; the structural characterization of the multi-gradient gel is shown Figure 3 As shown, it can be seen that the multi-gradient gel has shape gradient, modulus gradient and charge gradient at the same time.
[0159] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0160] Comparative Example 1
[0161] A non-gradient hydrogel, comprising the following components by mass ratio:
[0162]
[0163] The specific preparation steps are:
[0164] (1) Add 0.845 g lithium chloride, 6 g acrylamide, 2.4 g 2-acrylamide-2-methylpropanesulfonic acid, 0.06 g N,N-methylenebisacrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0165] (2) The precursor solution was injected into the ink cartridge of a multi-channel light-curing 3D printer to print a cylindrical gel with a radius of 10 mm and a height of 10 mm. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the uniform hydrogel. The schematic diagram of the obtained uniform hydrogel is shown in FIG. Figure 2 shown.
[0166] (3) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0167] Comparative Example 2
[0168] A multi-gradient hydrogel is prepared by first preparing four precursor solutions (named P1-P4), which include the following components in terms of mass ratio:
[0169]
[0170] The specific preparation steps are:
[0171] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0172] (2) The above solution was divided into 4 equal parts, and 0.15, 0.3, 0.45 and 0.6 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively. The mixture was stirred for 5 minutes in the dark. The mixtures were named P1-P4.
[0173] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0174] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0175] Comparative Example 3
[0176] A multi-gradient hydrogel is prepared by first preparing four precursor solutions (named P1-P4), which include the following components in terms of mass ratio:
[0177]
[0178] The specific preparation steps are:
[0179] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0180] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.006, 0.045, 0.03 and 0.015 g of N,N-methylenebisacrylamide were added respectively. The mixture was stirred for 5 minutes in the dark. The mixtures were named P1-P4.
[0181] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0182] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0183] Comparative Example 4
[0184] A multi-gradient hydrogel is prepared by first preparing four precursor solutions (named P1-P4), which include the following components in terms of mass ratio:
[0185]
[0186] The specific preparation steps are:
[0187] (1) Add 0.845 g lithium chloride, 6 g acrylamide and 0.03 g photoinitiator 1173 to 40 ml deionized water and stir for 5 minutes in the dark.
[0188] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively, and the parts were named P1-P4.
[0189] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the cone was 12 mm, the lower radius was 7.5 mm, the radius decreased by 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0190] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0191] Comparative Example 5
[0192] A multi-gradient hydrogel is prepared by first preparing four precursor solutions (named P1-P4), which include the following components in terms of mass ratio:
[0193]
[0194] The specific preparation steps are:
[0195] (1) Add 6 g of acrylamide and 0.03 g of photoinitiator 1173 to 40 ml of deionized water and stir for 5 minutes in the dark.
[0196] (2) The above solution was divided into 4 equal parts, and 0.6, 0.45, 0.3 and 0.15 g of 2-acrylamide-2-methylpropanesulfonic acid and 0.015, 0.03, 0.045 and 0.06 g of N,N-methylenebisacrylamide were added respectively, and the parts were named P1-P4.
[0197] (3) The P1-P4 precursor liquids were respectively injected into the ink cartridges of a multi-channel light-curing 3D printer, and a truncated cone-shaped gel was printed in layers. The upper radius of the truncated cone was 7.5 mm, the lower radius was 12 mm, the radius increment was 1.5 mm, and the height was 10 mm. From top to bottom, they were P1-P4, respectively. The polymerization conditions included: irradiation under ultraviolet light with a wavelength of 365 nm for 45 seconds to form the gel.
[0198] (4) The prepared gel was sandwiched between two gold electrodes and compressed by 30% at a frequency of 1 Hz. The open circuit voltage and short circuit current were tested using an electrometer. The test results are shown in Table 1.
[0199] Table 1
[0200]
[0201]
[0202] Test Example 1
[0203] The hydrogels provided in Example 7 are connected in series and in parallel, respectively, as shown in the schematic diagram. Figure 4 The electrical signal test results after the hydrogels are connected in series or in parallel are shown in Table 2.
[0204] Table 2
[0205]
[0206]
[0207] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A gel generator, characterized in that: The gel generator comprises two electrodes and a gel or gel array sandwiched between the two electrodes, wherein at least one of the modulus, charge concentration and equivalent diameter of the gel changes in a gradient from top to bottom, wherein: The gradient change of modulus includes: the cross-linking agent concentration is distributed in a gradient increasing manner from top to bottom; The changes in charge concentration include: the charge concentration is distributed in a gradient decreasing from top to bottom; The changes in the equivalent diameter include: the equivalent diameter increases gradually from top to bottom.
2. The gel generator according to claim 1, wherein: At least two of the modulus, charge concentration and equivalent diameter of the gel change in a gradient from top to bottom, preferably the equivalent diameter and modulus and / or charge concentration of the gel change in a gradient from top to bottom, more preferably the modulus, charge concentration and equivalent diameter of the gel change in a gradient from top to bottom; and / or The gel includes at least one of a hydrogel, an ionic gel, and an organic hydrogel, and is preferably a hydrogel.
3. The gel generator according to claim 1 or 2, wherein: The gradient change of the modulus includes: Based on the total mass of the polymer in the gel, the mass fraction of each gradient of the crosslinker in the gel is 0.1-5wt%, preferably the concentration increment of the crosslinker in adjacent gradients is 0.1-5wt%, more preferably the increment is 0.5-1wt%; and / or The gradient increase of the cross-linking agent concentration includes 2-8 levels of gradient increase, preferably 3-5 levels of gradient increase.
4. The gel generator according to any one of claims 1 to 3, wherein: The gradient change of the charge concentration includes: Based on the total mass of the polymer in the gel, the mass fraction of each charge concentration gradient is 0-50wt%, preferably the decreasing range of the charge concentration of adjacent gradients is 5-40wt%, more preferably the decreasing range is 10-15wt%; and / or The gradient decrease of charge concentration includes 2-8 levels of gradient decrease, preferably 3-5 levels of gradient decrease.
5. The gel generator according to any one of claims 1 to 4, wherein: The gradient change of the equivalent diameter includes: The equivalent diameter of each gradient is 7.5-20 mm, preferably the increment of adjacent equivalent diameters is 0.5-5 mm, more preferably the increment is 1-2.5 mm; and / or The gradient increase of the equivalent diameter includes 2-8 levels of gradient increase, preferably 3-5 levels of gradient decrease.
6. The gel generator according to any one of claims 1 to 5, wherein: The gel array is a series and / or parallel arrangement of 1 to 16 gels.
7. The gel generator according to any one of claims 1 to 6, wherein: The polymer in the gel is a polypropylene polymer and / or a polyethylene polymer, preferably at least one of polyacrylamide, polyvinyl alcohol, polyhydroxyethyl acrylate and polyacryloyl glycinamide; and / or The cross-linking agent is selected from at least one of N,N-methylenebisacrylamide, ethylene glycol diacrylate and ethylene glycol dimethacrylate, preferably N,N-methylenebisacrylamide; and / or The negative charge donor in the gel is at least one of 2-acrylamide-2-methylpropane sulfonic acid, sodium polystyrene sulfonate, sodium alginate, sodium polyacrylate, and hyaluronic acid, preferably 2-acrylamide-2-methylpropane sulfonic acid; and / or The gel contains ionic compounds.
8. The gel generator according to any one of claims 1 to 7, wherein: The electrode is at least one of a gold electrode, a carbon electrode, a platinum electrode, a silver electrode, a copper electrode, a stainless steel electrode and a glassy carbon electrode.
9. The method for preparing the gel generator according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: S1, preparing at least two groups of solutions by evenly dividing the gel monomer, the initiator, the ionic compound, the optional cross-linking agent, the optional negative charge donor and the solvent; or S1, preparing at least two groups of solutions by evenly dividing the gel monomer, the initiator, the ionic compound, the optional negative charge donor and the solvent, and adding a crosslinking agent to each group of solutions so that the concentration of the crosslinking agent in each group of solutions is different; or S1, preparing at least two groups of solutions by evenly dividing the gel monomer, initiator, ionic compound, optional cross-linking agent and solvent, adding a negative charge donor to each group of solutions, so that the concentration of the negative charge donor in each group of solutions is different; or S1, preparing at least two groups of solutions by evenly dividing the gel monomer, the initiator, the ionic compound and the solvent, and respectively adding a crosslinking agent and a negative charge donor to each group of solutions, so that the concentration of the crosslinking agent and the concentration of the negative charge donor in each group of solutions are different; S2, under polymerization conditions, forming each group of solutions in S1 into one body to obtain a gel having at least one of modulus, charge concentration and equivalent diameter changing in a gradient from top to bottom; S3. Sandwich the prepared gel between two electrodes.
10. The preparation method according to claim 9, wherein: The initiator is at least one of photoinitiator 1173, photoinitiator 2959 and photoinitiator 184; and / or The solvent is at least one of water, ionic liquid and organic solvent; and / or Based on the mass of the solvent used when feeding, the amount of the gel monomer is 10-30wt%; and / or Based on the mass of the gel monomer used when feeding, the amount of the initiator used is 0.1-1wt%; and / or The molar concentration of the ionic compound is 0.5-2 mol / L; and / or The polymerization conditions include: irradiation under ultraviolet light with a wavelength of 365nm for 30-60s.